SYSTEMATIC DEVELOPMENT OF FORMATIVE TEST IN ALGEBRA ACHIEVEMENT AMONG FORM FOUR STUDENTS USING THE RASCH MODEL AT SMK SIKUATI II, KUDAT - Hamzah Malajun; Mad Noor Madjapuni; Tan Choon Keong (Jurnal Penyelidikan Sains Sosial, 2021)
measuring instrumentsis very important to ensure that students can periodicallymeasure their level of achievement in a topic for each lesson that they have learned withsystematically. This research measures their level of development in algebra in learningmathematics via online using the self-regulated learning method at SMK Sikuati II, Kudat,Sabah. The researcher has produced a measuring instrument in the form of a 40-itemachievement test to periodically measure the development of student command in algebra.Instrument validity is done using the validation of experts in terms of content and construct.The reliability of the test is done by using the Rasch model which can assess the items’ level ofdifficulty and also the level of capability in obtaining correct answers for the next test items,where teachers and students can accurately assess the development of student command. Theimplication of this research is hoped to provide contributions in the context of development instudent topical command assessment, the usage of the Rasch model, improvement of teacherassessment instrument and increase of student achievement.